2013
DOI: 10.1007/s11307-013-0625-z
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Based Analysis of Amyloid-Burden Measured with [11C]PiB PET in a Double Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Voxel-based analysis of in vivo amyloid-β PET imaging studies in mouse models of Alzheimer's disease is feasible and allows studying the PiB retention patterns in whole brain maps. Furthermore, the selected approach in our study also allowed us to establish a quantitative relation between tracer retention and actual plaque pathology in the brain in a voxel-wise manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Thus far, reports using in vivo PET and MRI in transgenic animal models of AD using [ 11 10,11,21,24 . These approaches lack PET quantification or require transient opening of the blood-brain barrier for MRI contrast agents [2][3][4]8,25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, reports using in vivo PET and MRI in transgenic animal models of AD using [ 11 10,11,21,24 . These approaches lack PET quantification or require transient opening of the blood-brain barrier for MRI contrast agents [2][3][4]8,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…These approaches lack PET quantification or require transient opening of the blood-brain barrier for MRI contrast agents [2][3][4]8,25,26 . Quantifying the β-amyloid burden in small rodents is of paramount interest for the evaluation of new treatment strategies targeting β-amyloid; however, to our knowledge, there have only been a few encouraging reports on β-amyloid imaging using [ 11 C]PIB-PET in transgenic mice that have demonstrated the feasibility of this strategy 10,11,21,24 . Current in vivo MRI methodology is unable to quantify individual plaques in 3D data sets, especially in APPPS1 mice, which have a plaque diameter of ~2-22 µm 27 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, only few reports have demonstrated the feasibility of 11 C-PIB PET in fundamental research applications using smallanimal models of cerebral b-amyloidosis, although this method is gathering momentum (11,12,17,23). On the other hand, other groups have shown the feasibility of using high-resolution microscopic MR imaging to detect single amyloid plaques (1,9,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the feasibility of arterial spin labeling (ASL) MR imaging for the non-invasive quantification of rCBF in the brain of AD mice has been demonstrated (16) and specific 11 C-PIB binding has been compared with control animals using voxel-based analysis (17). However, to our knowledge, quantitative rCBF has never been compared with 11 C-PIB PET on a voxelwise basis in transgenic AD mice.…”
mentioning
confidence: 99%
“…Previous studies showed voxel-based analysis of amyloid plaques using PET 18 and MRI 13,19 in AD mouse models, which mostly focused on detecting amyloid plaques in the comparison of WT and AD mice. We showed the feasibility of our voxel-based method as a noninvasive imaging tool for detecting amyloid plaques to show the regional differences between WT and AD mice in the cerebral cortex and the hippocampus on D+1 and D+3 and to evaluate the effects of therapeutic drugs by comparing AD and drug-treated AD mice.…”
Section: Discussionmentioning
confidence: 99%